Capital Structure for Mature Family Companies in the Indonesian Stock Exchange - pandu adi cakranegara (International Journal of Family Business Practices, 2020)
Not all family companies choose to float on the Indonesian Stock Exchange. By being an open company an securities company must comply with various regulations from the supervisory institution that makes its various financial decisions limited by regulations and covenants. Limited financial decision making is a double-edged sword. On the one hand this can force the company to make more responsible decisions but on the other hand this independence can make the company lag behind other companies that are more flexible in making financial decisions. There are at least two parties that have an interest in the company's cash flow, namely the lender and the equity investor. On the one hand the company needs funds to carry out the company's plans. This study examines how firms choose capital structure and its impact on firms. The specialty in this study is the family company that has reached the established phase listed on the Indonesian Stock Exchange. The findings of this study are that mature family companies have a tendency to maximize cash flow and maintain a dominant position in capital structure and use short-term debt that is less binding or dealing with large banks.